2019
DOI: 10.1111/pce.13530
|View full text |Cite
|
Sign up to set email alerts
|

A purple acid phosphatase, GmPAP33, participates in arbuscule degeneration during arbuscular mycorrhizal symbiosis in soybean

Abstract: Arbuscules are the central structures of the symbiotic association between terrestrial plants and arbuscular mycorrhizal (AM) fungi. However, arbuscules are also ephemeral structures, and following development, these structures are soon digested and ultimately disappear. Currently, little is known regarding the mechanism underlying the digestion of senescent arbuscules. Here, biochemical and functional analyses were integrated to test the hypothesis that a purple acid phosphatase, GmPAP33, controls the hydroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 42 publications
2
32
0
Order By: Relevance
“…SlPAP20, which is homologous to GmPAP33 (Li et al ., ), may be involved in PLFA hydrolysis. We found that AM fungal inoculation significantly increased SlPAP20 expression at pH 6.5 but did not affect it at pH 4.5 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…SlPAP20, which is homologous to GmPAP33 (Li et al ., ), may be involved in PLFA hydrolysis. We found that AM fungal inoculation significantly increased SlPAP20 expression at pH 6.5 but did not affect it at pH 4.5 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Li et al . () demonstrated that a purple acid phosphatase (GmPAP33) participated in arbuscule degeneration via involvement in phospholipid hydrolysis in soybean; therefore, we additionally investigated the relative expression of a homologous gene ( SlPAP20 ). The sequences of the primers for all genes are described in Table S1, and the unpublished primers without known references, including those for genes RAM2 , STR , STR2 , SISUT1 , 2 , 4 , SISTP1 , LIN6 and SIPAP20 , were designed with Primer Premier Version 5.00 (http://www.premierbiosoft.com) in this study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, several mutant lines exhibited suppressed intraradical colonization, forming prematurely senescent or stunted arbuscules [11,31]. Some plant genes have been implicated in the cellular process of arbuscule degeneration [32][33][34][35]. The degeneration process of arbuscules has also been shown to be related to colonization level, illustrating the importance of arbuscule life cycle to the development of mycorrhiza.…”
Section: Latent Colonization Dynamics In Arbuscular Mycorrhizasmentioning
confidence: 99%